2016
DOI: 10.1080/00343404.2016.1163329
|View full text |Cite
|
Sign up to set email alerts
|

Inward Investment, Employment and Government Policies in Wales

Abstract: Cook M. and Fallon G. Inward investment, employment and government policies in Wales, Regional Studies. This empirical paper examines the links between multinational enterprises’ countries of origin, types of inbound foreign direct investment (IFDI), related capital investment levels and the resultant effects on regional employment in Wales, a peripheral region of the UK. Longitudinal, official data are used to examine the relationships between these variables, making use of statistical techniques. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A regional perspective of economic geography has contributed to the understanding of the geographical distribution of foreign direct investment (FDI) (Hong, 2007;Pelegrín & Bolancé, 2008;Tole & Koop, 2011) and its economic consequences within a given host country (Bajo-Rubio, Díaz-Mora & Díaz-Roldán, 2010;Wang et al, 2016). Studies have shown that, at the regional level, inward FDI can generate positive spillover on innovation (Smith & Thomas, 2017;Wang et al, 2016) and productivity (Bajo-Rubio et al, 2010), and can increase local employment (Cook & Fallon, 2016). Despite the important consequences of regional distribution of FDI, we do not fully understand its antecedents, namely, how regions within a country differ in their overall competitive profiles to attract and retain FDI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A regional perspective of economic geography has contributed to the understanding of the geographical distribution of foreign direct investment (FDI) (Hong, 2007;Pelegrín & Bolancé, 2008;Tole & Koop, 2011) and its economic consequences within a given host country (Bajo-Rubio, Díaz-Mora & Díaz-Roldán, 2010;Wang et al, 2016). Studies have shown that, at the regional level, inward FDI can generate positive spillover on innovation (Smith & Thomas, 2017;Wang et al, 2016) and productivity (Bajo-Rubio et al, 2010), and can increase local employment (Cook & Fallon, 2016). Despite the important consequences of regional distribution of FDI, we do not fully understand its antecedents, namely, how regions within a country differ in their overall competitive profiles to attract and retain FDI.…”
Section: Introductionmentioning
confidence: 99%
“…Such a regional explanation of MNEs location decision is currently missing in the economic geography literature, where research has primarily focused on the consequences of the regional distribution of FDI but not its antecedents (e.g. Bajo-Rubio et al, 2010;Cook & Fallon, 2016;Smith & Thomas, 2017). A few exemptions have attempted to link MNE location choice and agglomeration to regional conditions within a host country (Halvorsen, 2012;Hong, 2007;Meyer & Nguyen, 2005;Stallcamp et al, 2018).…”
Section: Introductionmentioning
confidence: 99%